The Power of Electronic Video Recording Proof in Crime Possession of Sharp Weapons - Abdulajid, Syawal (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study of “The Power of Electronic Video Recording Proof in Crime Possession of Sharp Weapons” focused on the power of electronic video recording proof. The aims of this study are to know the process of cases examination in Ternate District Court associated with the crime possession of sharp weapons namely video recording proof presented as evidence, and how the validity of video evidence as evidence and has the power of proof in the trial. This type of research is normative-empirical and uses secondary data as the main reference in analyzing data, the authors use qualitative descriptive analysis techniques that are based on applicable regulations and then adjusted to the reality that occurred in the field. Furthermore, in conclusion is done with deductive method that is analysis conducted with general knowledge to conclude things specifics. The results of the study showed that the proof of recording used as evidence in the crime possession of sharp weapons clearly not in accordance with criminal law procedure code (KUHAP), in the proving of crime possession of sharp weapons refer to Article 184 of KUHAP regarding legal evidence so that the evidence of the video recording is in principle merely as exhibit and cannot be used as evidence on the offense. Concerning the evidence presented in the hearing is the legally obtained evidence that is in accordance with applicable laws and regulations so that the proof has the evidentiary power to determine the defendant’s faults. In the case number: 286/Pid/2016/ Pn.Tte, and 279/Pid/2016/Pn.Tte, the recorded evidence presented is evidence obtained from the public then copied by the investigator and copied on the CD-R, so the opinion of the prosecutor as in his claim stating the guilt of the defendants has been proven legally and convincingly based on the evidence of the video recording is a mistake and undermines the basic principles of procedural law.